The Effect of Learning Discipline and Learning Independence on Economics Learning Outcomes of Class X Students - Fairus Refliana; Melya Pertiwi (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To find out whether there is an influence of learning discipline and learning independence on the economics learning outcomes of class X students of SMA Negeri 2 Kerinci. Methodology: This research is a quantitative research. And in accordance with the problems raised, this research is classified as Ex-Post Facto research. The population in this study were 122 class X students of SMA Negeri 2 Kerinci. The respondents taken in this study were 55 respondents (students). In this study, the tool used by researchers to collect data on variables X1 and X2 was by using a questionnaire or questionnaire, while the Y variable in this study was obtained from the results of daily tests for class X SMA Negeri 2 Kerinci students, documentation was taken to strengthen the data collection tool in this study. Data collection was carried out by distributing intelligence test questions to students of SMA Negeri 2 Kerinci. Prior to distributing the questions, the questions used must be good and appropriate or in other words the validity and reliability tests of the instrument have been carried out which can only then be presented to respondents. Respondents were asked to choose one answer by giving a checklist. Data analysis techniques, using normality, linearity and regression tests. Main Findings: There is a positive and significant influence between student learning discipline (X1) and student learning independence (X2) on economic learning outcomes (Y) of class X SMA N 2 Kerinci simultaneously with a calculated F value greater than Ftable (Fcount = 27.135> Ftable 3.20) with a significance of 0.000<0.05. The coefficient of determination = 0.511 gives an understanding of economic learning outcomes 51.1% is determined by Learning Discipline and Student Learning Independence in learning while the remaining 48.9% is explained by other factors not examined. This means that the better the student's learning discipline and the higher the student's learning independence will result in an increase in student economics learning outcomes. Novelty/Originality of this study: Knowing that there is a positive and significant influence between student learning discipline (X1) and student learning independence (X2) on economic learning outcomes (Y) class X SMA N 2 Kerinci.